The Effect Of Tiktok Shop Mykonos Official Live Streaming Marketing Communication On The Purchasing Power Of Students Of The Faculty Of Dakwah And Communication At Uin North Sumatera - Ichtisam, Muhammad Fathih; Sampurna, Ahmad (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah, Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study examines the impact of live streaming marketing messages on TikTok Shop Mykonos Official purchasing power among students at the Faculty of Da'wah and Communication, UIN North Sumatra. This study used a descriptive quantitative approach with a sample of 100 respondents. Purposive sampling involves selecting participants based on pre-determined criteria set by the researcher. A questionnaire was used to collect data on each indicator variable (X and Y). The research instrument test utilizes validity and normality checks, whereas the data analysis test employs simple linear regression analysis. It is well established that marketing communications via live streaming have a beneficial impact on students' purchasing decisions. The study found a significant impact of marketing messages on students' purchasing power (p-value = 0.006 < 0.05). This is due to live streaming's capacity to facilitate real-time interactions, foster trust, and give a more engaging and informative buying experience.